National treatment in the GATS: Corner-stone or Pandora's Box - Aaditya Mattoo (World Trade Organization (WTO), 1997)
This paper is concerned with three problems in the interpretation of the national treatment obligation in GATS. First, the precise domain of Article XVII on national treatment has not been clearly delineated, particularly in relation to Article XVI dealing with market access. Secondly, there is a conflict between the text of Article XVII and the structure of the schedules of commitments, which makes it difficult to interpret the scope of the national treatment obligation even for identical services supplied through different modes. The final, and most complex, problem arises in establishing the definition of like services and like service suppliers. Uncertainty about the precise meaning of the national treatment commitment may undermine the key GATS objective of creating a secure, predictable trading environment. Moreover, the extent of liberalization implied by the commitments under GATS depends on the precise choice of interpretation.
Keywords: F12; 330; national treatment; GATS; trade in services